UTILITY OF CYTODIAGNOSIS IN THE MANAGEMENT OF THYROID LESIONS - DR. PAVITHRA. P; DR. RASHMI. M. V. (International Journal of Pharma and Bio Sciences, 2014)
Fine needle aspiration cytology (FNAC) has become an accepted and cost effective procedure for preoperative diagnosis of thyroid lesions. Present study was carried out to study the spectrum of thyroid lesions on cytology and to evaluate the diagnostic accuracy of FNAC in palpable thyroid lesions by comparing with histopathology wherever available. Total of 250 cases of thyroid swellings were aspirated over a period of 5 years in a tertiary care hospital. Cytologically, the cases were classified into 5 groups, namely, benign, inadequate, suspicious, malignant and cellular follicular lesions. There were 221 benign cases, 11 malignant, 2 suspicious, 6 inadequate and 10 with cellular follicular lesions. FNAC reports were compared with histopathology results and statistical indices were calculated. The sensitivity, specificity and diagnostic accuracy were 75.86% & 58.82%, 100% & 76.47% and 89.70% & 72.05% respectively considering suspicious cases alternatively as positives and negatives. FNAC is a highly sensitive and specific test with high diagnostic accuracy for preoperative evaluation of patients with thyroid swelling.